Step
*
1
of Lemma
sub-bag-filter3
1. T : Type
2. p : T ⟶ 𝔹
3. b : bag(T)
4. c : bag(T)
5. cs : bag(T)
6. c = (b + cs) ∈ bag(T)
⊢ [x∈c|p[x]] = ([x∈b|p[x]] + [x∈cs|p[x]]) ∈ bag(T)
BY
{ ((HypSubst' (-1) 0 THENA Auto) THEN RWO "bag-filter-append" 0 THEN Auto) }
Latex:
Latex:
1.  T  :  Type
2.  p  :  T  {}\mrightarrow{}  \mBbbB{}
3.  b  :  bag(T)
4.  c  :  bag(T)
5.  cs  :  bag(T)
6.  c  =  (b  +  cs)
\mvdash{}  [x\mmember{}c|p[x]]  =  ([x\mmember{}b|p[x]]  +  [x\mmember{}cs|p[x]])
By
Latex:
((HypSubst'  (-1)  0  THENA  Auto)  THEN  RWO  "bag-filter-append"  0  THEN  Auto)
Home
Index